2018
DOI: 10.1101/397729
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning 2-in-1: Towards Integrated EEG-fMRI-Neurofeedback

Abstract: Neurofeedback (NF) allows to exert self-regulation over specific aspects of one's own brain function by returning information extracted in real-time from brain activity measures. These measures are usually acquired from a single modality, most commonly EEG or fMRI. EEG-fMRI-neurofeedback (EEG-fMRI-NF) is a new NF approach that consists of providing a NF based simultaneously on EEG and fMRI. By exploiting the complementarity of these two modalities, EEG-fMRI-NF opens a spectrum of possibilities for defining bim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 100 publications
(113 reference statements)
2
43
0
Order By: Relevance
“…Methods and protocol for the second study have been described in 18 and are schematically showed in Figure 2. As for the first study, the experimental procedure and the NF task were carefully explained to participants before and during the experiment, in the form of written and verbal instructions.…”
Section: Xp2 (Data Citation 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Methods and protocol for the second study have been described in 18 and are schematically showed in Figure 2. As for the first study, the experimental procedure and the NF task were carefully explained to participants before and during the experiment, in the form of written and verbal instructions.…”
Section: Xp2 (Data Citation 2)mentioning
confidence: 99%
“…Data collected during the MIpre session were used to identify an optimal spatial filter for EEG and a ROI based on the maximum of activation in the target motor area. As described in detail in 18 , EEG data were pre-processed in Analyzer (Brain Product Software) and BCG artefacts were corrected with a semi-automated procedure. A Common Spatial Pattern (CSP) filter maximizing the difference in EEG power in the target band Hz) between rest and MI blocks was estimated from a selection of motor channels.…”
Section: Xp2 (Data Citation 2)mentioning
confidence: 99%
“…The neurofeedback display was uni-dimensional (1D) for 9 subjects (Figure 3 left), and bi-dimensional (2D) for 8 subjects (Figure 3 middle). For both, the goal was to bring the ball into the dark blue area (Perronnet et al, 2018).…”
Section: Data Acquisition and Pre-processingmentioning
confidence: 99%
“…The Figure 3. Bi-modal neurofeedback strategies (1D on the left, 2D on the middle), displayed during sessions (Perronnet et al, 2018). 1D: the ball's position represents the sum of y e and y f .…”
Section: Data Acquisition and Pre-processingmentioning
confidence: 99%
See 1 more Smart Citation